Clinicopathological features of squamous cell carcinoma of the oral cavity and oropharynx in young patients. Issue 4 (May 2018) - Martinez, R.C.-P.; Sathasivam, H.P.; Cosway, B.; Paleri, V.; Fellows, S.; Adams, J.; Kennedy, M.; Pearson, R.; Long, A.; Sloan, P.; Robinson, M.
Abstract: Our aim was to examine the clinicopathological features of squamous cell carcinoma (SCC) of the oral cavity and oropharynx in a group of young patients who were dignosed during a 15-year period (2000–2014). Patients' clinical details, risk factors, and survival were obtained from medical records. Formalin-fixed, paraffin-embedded, tissue was tested for high-risk human papillomavirus (HPV). The results were compared with those of a matching group of older patients. We identified 91 patients who were younger than 45 years old, and the 50 youngest patients were studied in detail. The male:female ratio was 2:1, with more tumours located in the oral cavity than in the oropharynx (35 compared with 15). HPV-related SCC was restricted to the oropharynx. When matched for site, stage and HPV status, five-year overall survival was similar in young and matched older patients (log-rank test, p = 0.515). Our findings suggest that young patients with oral SCC have a disease profile similar to that of older patients with the condition. It is plausible that prognostic information generally available for oral cancers is applicable to young patients with the disease.